Misoprostol versus Placebo for Unsatisfactory Colposcopic Finding: A Randomized Controlled Trial - Reuthairat Tungmunsakulchai; Maleechat Sripipattanakul (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective: To assess the effectiveness of vaginal misoprostol for converting unsatisfactory to satisfactory colposcopy.Materials and Methods: Forty women with abnormal cervical cytology and unsatisfactory colposcopy who underwent colposcopic examination at colposcopic clinic Khon Kaen Hospital, between May, 2009 and June, 2010. Patients were randomly allocated to received either 200 μg misoprostol or placebo vaginally, and colposcopic examination were taken 4 hours later. The percentage of conversion to satisfaction result and the adverse effects were recorded.Result: There were 20 women in each misoprostol and placebo group. One patient was excluded from each group because of follow up problem. In misoprostol group, 13 out of 19 patients (68.4%) were converted into satisfactory colposcopy result compared with five out of 19 patients (26.3%) in placebo group. This effect was statistically significant difference (P=0.009). No serious adverse effects was reported in both groups. Conclusions: Two hundred micrograms of vaginal misoprostol was effective and safe to convert unsatisfactory to satisfactory colposcopy result.